2017
DOI: 10.1186/s12986-017-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol regulates body weight in healthy and ovariectomized rats

Abstract: ObjectiveThe elevated body weight in post-menopausal state attributes to the reduced estrogen levels which is alleviated by resveratrol (RES) but its role in control rats is not well understood. The main objective of the study was to explore the effects of RES on the body weight of ovariectomized (OVX) female rats with controls and to relate their biochemical parameters.MethodsFemale Wistar rats weighing 200–300 g underwent bilateral ovariectomy (OVX) and were fed soya free diet (n = 8 rats per group). In all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…Ovariectomy causes body weight gain in rats [ 41 ]. Ovariectomized rats reported gaining fat, specifically visceral fat [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovariectomy causes body weight gain in rats [ 41 ]. Ovariectomized rats reported gaining fat, specifically visceral fat [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RSV has an estrogen-like effect by activating estrogen receptors at nuclear and extracellular levels [53]. Recently, RSV has shown better effects on metabolic parameters in female controls than in ovariectomized female rats [54]. It would, therefore, be interesting to assess the effects of RSV on ovariectomized female GK rats to better understand the involvement of hormones in cardiovascular RSV effects.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, Chen et al (2017) also reported that RES (400 mg/kg/day) treatment for three months provided protection against diet-induced dyslipidemia in C57BL/6 mice. Studies have demonstrated that RES treatment has fat mobilization and antiobesity effects in rodents ( Baile et al, 2011 ), and also significantly reduced the body weight gain of female Wistar rats and ovariectomized female Wistar rats ( Sharma, Sharma & Thungapathra, 2017 ). In this study, we observed that the RES intervention did not significantly reduce the body weight of mice; however, we detected a trend of reduced body weight in mice treated with RES.…”
Section: Discussionmentioning
confidence: 99%